Time series analysis of dengue cases reporting to a tertiary care hospital - Kembhavi, Ravindra S.; U. S., Saurabha (International Journal Of Community Medicine And Public Health, 2019)
Background: Dengue fever is a major public health problem, the concern is high as the disease is closely related to climate change. Methods: This was a retrospective study, conducted for 1 year in a tertiary care hospital in the city of Mumbai. Data of Dengue cases and climate for the city of Mumbai between 2011 and 2015 were obtained. Data was analysed using SPSS- time series analysis and forecasting model. Results: 33% cases belonged to the 21-30 years, proportion of men affected were more than women. A seasonal distribution of cases was observed. A strong correlation was noted between the total number of cases reported and (a) mean monthly rainfall and (b) number of days of rainfall. ARIMA model was used for forecasting. Conclusions: The trend analysis along with forecasting model helps in being prepared for the year ahead.